ChemInform Abstract: Facile Synthesis of 4, 5, 6a, 7‐Tetrahydrodibenzo[de, g]chromene Heterocycles and Their Transformation to Phenanthrene Alkaloids. Issue 9 (4th March 2014) - Kapadia, Nirav; Harding, Wayne
Abstract A microwave assisted and Pd‐catalyzed oxa‐Pictet Spengler reaction is developed to synthesize tetracyclic isochromane derivatives (IV).